Off the grid!, (N)either roof (N) or floor - E. Y. Prasetyo; D. L. Putra; D. Apriargo (IPTEK Journal of Proceedings Series, 2017)
To construct a place, one may consider creating a shelter, or a ground plane that would accommodate people’s activities. Located in suburban part of the city of Surabaya, area of Tambaksari with its dense population is lacking for such a place. There are two fundamental requirements to raise the quality of living in the area. Provide a sheltered space for communal and a confined space for the youth playground and recreational activities are the two requirements. Two activities that was scattered at the beginning. For such, we proposed a single slab of concrete to accommodate both requirements. Which the slab will serve as a roof for the street vendors as a trigger for people to gather on the ground floor, and its also serve as a ground plane for playground on the upper floor. Connected with a continuous ramp and large voids, both activities on different floor will be interrelated both visually and physically. An important note in this project is to present the centralization of street vendors, which is naturally reluctant to be centralized, its unique qualities such as the randomness, the complexity, less-perceived boundary onto the site leads to irregular concrete slab shape decision to accommodate such uniqueness. Irregular shape ultimately becomes a problem for conventional structural grid. Parameterized random position of column then applied to the area of the floor. Furthermore triangular grid are introduced to connect the column as structural beam. The result is uncommon form both aesthetically and structurally piece of architecture.